1987
DOI: 10.1056/nejm198711263172204
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Pneumonia in Intubated Patients Given Sucralfate as Compared with Antacids or Histamine Type 2 Blockers

Abstract: Gram-negative nosocomial pneumonia may result from retrograde colonization of the pharynx from the stomach, and this may be more likely when the gastric pH is relatively high. We studied the rate of nosocomial pneumonia among 130 patients given mechanical ventilation in an intensive care unit who were receiving as prophylaxis for stress ulcer either sucralfate (n = 61), which does not raise gastric pH, or conventional treatment with antacids, histamine type 2 (H2) blockers, or both (n = 69). At the time of ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
140
2
7

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 711 publications
(152 citation statements)
references
References 30 publications
3
140
2
7
Order By: Relevance
“…The results of this study confirm that intragastric microbial growth is pH-dependent [18][19][20] and promoted by treatment with Hs-receptor blockers or antacids [3][4][5][6][7][8]. However, our data do not support results from previous studies on intubated ICU patients, which suggested that gastric colonization was a significant risk factor for subsequent tracheal colonization or pneumonia [5,[8][9][10].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…The results of this study confirm that intragastric microbial growth is pH-dependent [18][19][20] and promoted by treatment with Hs-receptor blockers or antacids [3][4][5][6][7][8]. However, our data do not support results from previous studies on intubated ICU patients, which suggested that gastric colonization was a significant risk factor for subsequent tracheal colonization or pneumonia [5,[8][9][10].…”
Section: Discussioncontrasting
confidence: 87%
“…However, none of the three reports mentioned oropharyngeal culturing, so the oropharynx as an important source of pathogens [21][22][23] may have contributed to gastric and tracheal colonization in all three studies. Treatment with H zreceptor blockers or antacids may predispose to pneumonia in intubated patients [7,11,12), but the * DIC score as defined [16], ranging from 0 to 13; 13 = most severe DIe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mechanisms include: 1) disturbance of the physiological pharyngoglottal reflexes that prevent aspiration [22]; 2) dysfunction of the upper and lower oesophageal sphincters and associated gastro-oesophageal reflux secondary to the presence of the tube [9]; and 3) colonisation of the stomach by bacteria that may subsequently migrate to the oropharynx and into the lower respiratory tract (gastropulmonary hypothesis) [23,24].…”
Section: Discussionmentioning
confidence: 99%